PENGARUH SERBUK DAUN RIMAU (Toona sinensis Roem.) TERHADAP KEMATIAN LARVA ULAT GRAYAK (Spodoptera litura F.) - Rizal, Syamsul (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2014)
Research to determine the effect of leaf powder Rimau (Toona sinensis Roem.) To death army worm larvae (Spodoptera litura F.) was conducted in August 2013 at the Forestry Research InstituteÂ  Palembang. The results shows Rimau leaf powder can cause death armyworm larvae and relatively less toxic. Key words: leaf powder Rimau, army worm larvae